I, You, He, We and They Can Be Resilient - Franco A., Luz Dary; Urrea O., Ruth Yolanda (Rastros Rostros, 2012)
Early childhood is the crucial stage for the family and the school to ensure that children strengthen their levels of resilience, which will enable them to engage in the future life with a proper preparation in the face of difficult or risky situations. This paper reports on the progress made in the research, which originated at the Universidad del Tolima, entitled “Proposal for a Program to Increase the Levels of Resilience in First Grade Children of the Instituto Tecnológico Salesiano Eloy Valenzuela Sede C of Bucaramanga”. This project is based on the analysis of backgrounds, and the previous conclusions are the result of fieldwork that aims to establish the aspects that should include the program that strengthens resilience, final product of the research.